Implementation of the 2018 Classification of Periodontal Diseases: A Questionnaire-Based Survey - Zarenti, Sofia; Doufexi, Aikaterini Elisavet; Batas, Leonidas; Chatzopoulou, Domniki; Gillam, David; Mardas, Nikos; Sakellari, Dimitra (European Journal of Dentistry, 2025)
The new classification of periodontal and peri-implant diseases and conditions (2018) includes definitions of the respective diseases, modifications, and new additions to the 1999 classification. The purpose of the study was to present the opinion and level of understanding of Greek dentists regarding the new classification and to determine the approach for its establishment.A questionnaire consisting of 26 multiple-choice questions was distributed to Greek dentists in paper or digital form.Data were collected, recorded using Microsoft Excel, and were analyzed with SPSS 29.0 (IBM, United States).A total of 203 questionnaires were collected (49.3% male/50.2% female; mean age 39.02 years). 36.8% of the participants exclusively practiced periodontology and 44.8% general dentistry. Seventy-one participants were members of the Hellenic Society of Periodontology (HSP). 58.9% used the old classification system, which is reported as preferred by 53.5% of HSP members. Also, 53.3% of participants characterized the new classification as difficult to be applied, 47.1% of whom were HSP members. The most frequent reason for not using it (63/133) was the convenience of the older system application. A statistically significant higher percentage of HSP members correctly answered the comprehension questions (diagnostic criteria and clinical cases) of the questionnaire (z-test with Bonferroni correction < 0.05). Note that 79.7% of the participants stated that they should improve their knowledge regarding the new classification, mainly through seminars/courses.Most Greek dentists appear not to implement the 2018 classification system due to reported difficulty in understanding, while recognizing the need to comprehend and apply it to their clinical practice.
Keywords: classification; periodontal diseases; questionnaire; diagnosis